Torque control analysis of platform based end effector ankle foot orthosis for rehabilitation - Abdul Haleem, Habeeb Mohamed; Muhammad Aizzat, Zakaria (Penerbit UMP, 2019)
This paper presents the control of a one degree of freedom for lower limb platform based end effector ankle foot orthosis for rehabilitation. The plant of the system is obtained through system identification approach and a proportional-integral (PI) architecture is employed to investigate its efficacy in performing joint-space control objectives namely the dorsi-plantar flexion of the ankle joint. It was found from the study that the PI performed well against the torque control parameter for the system. Variation of load was tested as a disturbance to the system to check the system stability.